RELEVANSI LULUSAN PERGURUAN TINGGI DI INDONESIA DENGAN KEBUTUHAN TENAGA KERJA DI ERA GLOBAL - Titik Handayani (Jurnal Kependudukan Indonesia, 2015)
Global labor market which marked by the integration of labor between countries is also accompanied by the emergence of variety kind of new job along with the science-technology innovation and also creativity improvement to answer the increasingly fierce competition. Therefore, the higher education are demanded more to be able to respond the workforce needs that more dynamic and complex. Based on those issues, this paper will examine the relevance of university graduates in Indonesia and labor requirement in the global era. The used approach is a quantitative approach using secondary data from various sources such as the Directorate General of Higher Education of the Ministry of Education, the Central Bureau of Statistics, ILO and the World Bank and several studies are relevant.Based on the macro data, it shows that Indonesia currently has a tendency in opened the new Higher Education (PT) massively and more profit oriented without being followed by the provision of adequate infrastructure and quality, and then resulting the increasing number of graduates. On the other hand, productive employment in Indonesia is also limited, so that the educated unemployed are relatively high. Another problem, McKinsey Global Institute (MGI) predicts that in the global labor market, in 2030 Indonesia is expected to experience a labor shortage of educated and skilled, but has excess in non-skilled labor. The gap between supply and demand in educated and skilled labor also supported by the ILO data (2015) about the labor who does not fulfill the education and skills qualification, which the proportion is more than half. Those issues are getting urgent to be solved, along with the implementation of ASEAN Economic Community and other regional agreement globally. This is because the lack of workforce will be immediately filled by foreign workers. Therefore, the cooperation and synergy between Higher Education (PT) and the world of business and industry, both national and international, need to be improved.